Early Feasibility Testing and Engineering Development of the Transapical Approach for the HeartWare MVAD Ventricular Assist System - Tamez, Daniel (2014)
Implantation of ventricular assist devices (VADs) for treatment of end-stage heart failure (HF) falls decidedly short of clinical demand, which exceeds 100,000 HF patients per year. VAD implantation often requires major surgical intervention with associated risk of adverse events and long recovery periods. To address these limitations, HeartWare, Inc. (Miami Lakes, FL) has developed a platform of miniature ventricular devices with progressively reduced surgical invasiveness and innovative patient peripherals. One surgical implant concept is a transapical version of the miniaturized left ventricular assist device (MVAD). The HeartWare MVAD Pump® is a small, continuous flow, full-support device that has a displacement volume of 22mL. A new cannula configuration has been developed for transapical implantation, where the outflow cannula is positioned across the aortic valve. The two primary objectives for this feasibility study were to evaluate anatomic fit and surgical approach and efficacy of the transapical MVAD configuration. Anatomic fit and surgical approach were demonstrated using human cadavers (n=4). Efficacy was demonstrated in acute (n =2) and chronic (n = 1) bovine model experiments and assessed by improvements in hemodynamics, biocompatibility, flow dynamics, and histopathology. Potential advantages of the MVAD Pump include flow support in the same direction as the native ventricle, elimination of cardiopulmonary bypass, and minimally-invasive implantation.